Penguatan Pemberdayaan Masyarakat Kecamatan Semau melalui Pelatihan Pemasaran Potensi Wisata di Wilayah Kecamatan Semau - Chrystia Aji Putra; Zainal Abidin Achmad; Angelita Kracibaya Nauli Panggabean; Novia Kurniasari (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This research assesses the strengthening of community empowerment in Semau District, East Nusa Tenggara, through digital marketing training to optimize local tourism potential. The training includes the use of the Canva application for promotional design, village registration on the Village Tourism Network platform (Jadesta), and the establishment of the Semau Tourist Information Center (S-TIC). The results of the training indicate an improvement in digital skills among village cadres and the effective establishment of the S-TIC. However, administrative challenges such as the lack of Village Tourism Decrees hinder registration in Jadesta. This effort is expected to enhance visibility and economic well-being, as well as ensure sustainable tourism development in the Semau District.